Identification of Environmental Risk Factors Associated With the Development of Inflammatory Bowel Disease. (23rd June 2020) - van der Sloot, Kimberley W J; Weersma, Rinse K; Alizadeh, Behrooz Z; Dijkstra, Gerard
Abstract: Background and Aims: Multiple genetic and environmental factors are involved in the aetiology of inflammatory bowel disease [IBD] including Crohn's disease [CD] and ulcerative colitis [UC], but data on these exposome factors are difficult to identify. Several exposome factors such as smoking have been shown to be involved; as for other environmental factors, eg stress, results have been conflicting. Methods: We performed a case-control study including 674 IBD patients of the 1000IBD cohort, frequency-matched based on sex and age with 1348 controls from the population-based Lifelines Cohort Study. Exposome data were obtained using the validated Groningen IBD Environmental Questionnaire [GIEQ], capturing exposome factors through different stages of life using 844 items, of which 454 were applicable to study the role of 93 exposome factors in disease aetiology. Logistic regression [LR] modelling with Bonferroni correction for multiple testing was applied to estimate the multivariable-adjusted effect of each exposome factor. Results: For IBD, we identified four novel factors: stressful life events (CD odds ratio [OR] 2.61/UC OR 2.92), high perceived stress [2.29/2.67], alcohol use [0.40/0.43], and bronchial hyper-reactivity [3.04/2.36]. Four novel factors were associated with only CD: prenatal smoke exposure [1.89], having a bed partner [0.53], allergies [2.66], and cow's milk hypersensitivity [5.87]; and two solely with UC: carpet flooring [0.57] and neuroticism [1.32]. Nine factors were replicated. Conclusions: In this study we identified 10 novel, and replicated nine previously reported, exposome factors associated with IBD. Identifying these factors is important for both understanding disease aetiology and future prevention strategies to decrease the development of IBD in genetically susceptible persons.